Hormone Receptors and Age Distribution in Breast Cancer Patients at a University Hospital in Northern Egypt. (January 2013) - Hussein, Osama; Mosbah, Mahmoud; Farouk, Omar; Farag, Kamel; El-Saed, Aiman; Arafa, Mohammad; Abdallah, Ahmed
Introduction: Breast cancer is the most common cancer among Egyptian women. The disease is often advanced at diagnosis. Since molecular profiling is not feasible in routine practice, we sought to examine the association of age distribution with hormone receptor profile, disease stage and outcome among Egyptian women. Patients and Methods: We conducted a retrospective review of breast cancer patients treated at Mansoura University Cancer Center in the Nile Delta from 2006 through 2011. Age groups were examined in relation to hormone receptors status and tumor clinicopathological criteria. Additionally, the effect of receptor status on disease relapse and disease-free survival was examined with logistic regression and Kaplan–Meier analysis. Results: A total of 263 patients were included in the current analysis. About 66.9% (n = 176) of patients were hormone receptor positive, 14.1% (n = 37) were Her2 /neu positive, and 19.0% (n = 50) were triple negative. Median age of the patients was 52 years and was equal across all receptor status types. Triple negative status correlated with increased risk of disease relapse (odds ratio = 1.8, P = 0.03) and with shortened disease-free survival (hazards ratio = 2.6, P < 0.01). Conclusion: The age distribution and receptor status pattern in the Nile Delta region does not explain the aggressive behavior of the disease. The age of the patients at diagnosis is older than patients in earlier studies from Egypt emphasizing the importance of implementing mammographic screening programs.